Novel bionic inspired nanosystem construction for precise delivery of mRNA - Yang, Taihua; Xia, Lei; Li, Gen; Zhao, Jie; Li, Jie; Ge, Jiahao; Yuan, Qinggong; Zhang, Jianjun; He, Kang; Xia, Qiang (Frontiers in Bioengineering and Biotechnology, 2023)
The intracellular delivery of messenger (m)RNA holds great potential for the discovery and development of vaccines and therapeutics. Yet, in many applications, a major obstacle to clinical translation of mRNA therapy is the lack of efficient strategy to precisely deliver RNA sequence to liver tissues and cells. In this study, we synthesized virus-like mesoporous silica (V-SiO2) nanoparticles for effectively deliver the therapeutic RNA. Then, the cationic polymer polyethylenimine (PEI) was included for the further silica surface modification (V-SiO2-P). Negatively charged mRNA motifs were successfully linked on the surface of V-SiO2 through electrostatic interactions with PEI (m@V-SiO2-P). Finally, the supported lipid bilayer (LB) was completely wrapped on the bionic inspired surface of the nanoparticles (m@V-SiO2-P/LB). Importantly, we found that, compared with traditional liposomes with mRNA loading (m@LNPs), the V-SiO2-P/LB bionic-like morphology effectively enhanced mRNA delivery effect to hepatocytes both in vitro and in vivo, and PEI modification concurrently promoted mRNA binding and intracellular lysosomal escape. Furthermore, m@V-SiO2-P increased the blood circulation time (t1/2 = 7 h) to be much longer than that of the m@LNPs (4.2 h). Understanding intracellular delivery mediated by the V-SiO2-P/LB nanosystem will inspire the next-generation of highly efficient and effective mRNA therapies. In addition, the nanosystem can also be applied to the oral cavity, forehead, face and other orthotopic injections.